2005
DOI: 10.2486/indhealth.43.663
|View full text |Cite
|
Sign up to set email alerts
|

Early Biochemical Alterations in Manganese Toxicity: Ameliorating Effects of Magnesium Nitrate and Vitamins

Abstract: Manganese-induced early biochemical changes and effects of supplementation of magnesium nitrate (Mg(NO 3 ) 2 ) and antioxidant vitamins (A, C, D and E) were studied in rats intoxicated with manganese. Significant elevation in the level of chlorides in plasma, erythrocytes, liver and cerebellum, and a decrease in plasma inorganic phosphate (pi) with an increase in liver pi were observed in animals exposed to manganese as compared to controls. The level of erythrocyteacid labile phosphate (ALP), nicotinamide ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, in this study 61 days of treatment with zinc only had a limited effect on decreasing cortical manganese concentrations. One study reported that magnesium could protect against manganese toxicity 16 . However, whether magnesium can be used to treat HE has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study 61 days of treatment with zinc only had a limited effect on decreasing cortical manganese concentrations. One study reported that magnesium could protect against manganese toxicity 16 . However, whether magnesium can be used to treat HE has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated magnesium levels we found with melatonin supplementation in the group 6 (melatonin-supplemented diabetic swimming) in our study maight be evaluated as a striking result, in consideration of the effects of this element in the glucose metabolism (20,21). Physical activity was shown to result in an increase in manganese activity in rats (22) However, it is also known that excessive accumulation of manganese causes lipid peroxidation through a toxic effect (23). Therefore, elevated manganese levels we established in the diabetes groups are important with respect to the relation between diabetes and lipid peroxidation.…”
Section: Tab 3 Levels Of Copper Iron Calcium Zinc and Selenium Imentioning
confidence: 97%